The relationships between big five personality model and student performance level among OM221 students in UiTM Jengka Pahang / Anitah Haris, Nur Munira Harun and Rozaimah Harun - Haris, Anitah; Harun, Nur Munira; Harun, Rozaimah (2012)
The purpose of this study was to investigate the relationship between Big Five Personality model and student performance level among OM221 student in UiTM Pahang. This correlational study used a cluster sampling technique. The methodology used in this study was survey questionnaires which were distributed to 50 respondents that are involved the student OM221 in UiTM Pahang itself, the respondent are taken from starting on Part 2 until Part 6 student, this group are taken because the respondent need to give the information about their previous result (CGPA) and it was not suitable to be answered by Part 1 student. The questionnaires were analyzed using SPSS 18. The major finding in this study indicated that there was only certain of personality characteristic in Big Five Personality model have a significant relationship and can describe well the student OM211 performance. Based on the findings personality of Conscientiousness in the most significant and can describe well the student performance and personality of Openness to the Experience is the insignificant variable and cannot describe well the student performance. Generally the student performance is at the range of 3.00-3.49 CGPA. This study also highlighted several recommendations to further improvement of student performance. Among the suggestions are to be improve is the action from the student, lecturers and until to the faculty itself. A few suggestions for a future research also are indicate in the study which is might help the future researcher in order to make another study.